Final Fate of Cancer Cells After Nuclear Genetic Material Damage - Lei WANG; Xiaomin XU; Jian WANG; Fangzheng MOU; Darong WEI (Zhongliu Fangzhi Yanjiu, 2024)
Cancer cells refer to a group of malignant cells with strong division and proliferation abilities. Cancer cells rely on the unstable plunder of human nutrition to sustain the large amount of energy that they need for their own division and proliferation. The division and proliferation of cancer cells are linked to the synthesis and replication of genetic material in the nucleus. Blockage or destruction of the synthesis of genetic material in cancer cells is one of the mechanisms underlying the action of most antitumor drugs. As the key material that dominates cell division, proliferation, and death, nuclear genetic material which mainly refers to the deoxyribonucleic acid located on the chromatin in the nucleus, plays a decisive role in the final fate of cells. The final fate of cancer cells after the damage of the genetic material is worthy of investigation and analysis. In this paper, we discuss and analyze the fate of cancer cells after genetic material damage from the aspect of cellular cycle arrest, apoptosis, autophagy, and senescence to provide ideas for the mechanism research on antitumor drugs.